Leonardo as a visual communication theorist. Principles of written/graphic/visual communication in Leonardo da Vinci's Notebooks - Leonardo Romei (Ocula)
This article is devoted to outlining a theory of graphic/written communication in the frame of a visual communication paradigm in Leonardo da Vinci's notebooks. He practiced a continuous integration between different tools of expression and described a printing technique that was able to preserve this complexity. His notes on the relationship between words and images are few, especially when compared with the notes on differences between them. However, with a patient approach, systematizing previous works and thanks to new examples and lexical clarification, it is possible to outline a structured vision that allows us to put Leonardo in the conceptual equipment of any theorist of communication.